2017
DOI: 10.1007/s00586-017-5118-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel 3D drill template for cervical pedicle screw tunnel design: a cadaveric study

Abstract: The 3D CT reconstructive rapid prototyping drill template combined with the screw tunnel design based on 3D cutting technique can help facilitate accurate cervical pedicle screw insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Pedicle screws show an improved biomechanical stability over lateral mass screws, allowing for shorter instrumentations with improved reposition capacities 5,6 . However, safety concerns regarding injury to the vertebral artery, spinal cord or nerve root have been reported 7,8 . Furthermore, cervical pedicle diameters are smaller than those in the thoracic or lumbar spine, increasing its technical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Pedicle screws show an improved biomechanical stability over lateral mass screws, allowing for shorter instrumentations with improved reposition capacities 5,6 . However, safety concerns regarding injury to the vertebral artery, spinal cord or nerve root have been reported 7,8 . Furthermore, cervical pedicle diameters are smaller than those in the thoracic or lumbar spine, increasing its technical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, according to the reports of relevant clinical experiments, the drill guide template has been successfully applied in the placement of pedicle screws in spine surgeries [7][8][9]. Some studies have shown that patientspecific drilling guidance templates can reduce the incidence of pedicle screw misplacement and decrease the operative time and intraoperative blood loss; however, most of these studies involved animal experiments and cadaver specimen experiments [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared with traditional C2 pedicle screw placement, the 2 methods can accurately set the placement point and direction of the C2 pedicle screw and effectively increase the accuracy of C2 pedicle screw placement. Yu et al [21] proved the safety and effectiveness of 3D-printed navigation templates based on 3D models of the cervical spine through cadaver studies, and this technology can achieve accurate C2 pedicle screw placement. Singh et al [22] showed that intraoperative navigation significantly improved the accuracy of C2 pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%